Kontribusi Perilaku Kepemimpinan terhadap Loyalitas Kerja Guru SMA Swasta Se-Kecamatan Cibungbulang - Richa Nurlaela; Ima Rahmawati; Hana Lestari (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
Teacher work loyalty is a measure of loyalty which is described by the ability of employees to defend and maintain the company / organization both in the area and outside the work area. This study aims to determine the contribution of leadership behavior to teacher job loyalty. This research was conducted in private high schools throughout Cibungbulang District. The number of samples taken was 25 teachers, with a non-probability sampling method with a sampling technique, namely saturated samples. This research uses a quantitative approach with a survey method. Data collection techniques using a questionnaire or questionnaire. The data analysis technique used is simple linear regression. Based on the results of the analysis, it shows that there is a contribution between leadership behavior and teacher work loyalty. This shows that the stronger the influence of leadership behavior, the higher the job loyalty generated by the teacher. Therefore, to foster job loyalty to teachers, a leader is expected to further improve leadership behavior in order to increase teacher job loyalty..